SARS-CoV-2 Infections and ACE2: Clinical Outcomes Linked With Increased Morbidity and Mortality in Individuals With Diabetes - Obukhov, Alexander G.; Stevens, Bruce R.; Prasad, Ram; Li Calzi, Sergio; Boulton, Michael E.; Raizada, Mohan K.; Oudit, Gavin Y.; Grant, Maria B. (Diabetes (New York, N.Y.), 2020)
Individuals with diabetes suffering from coronavirus disease 2019 (COVID-19) exhibit increased morbidity and mortality compared with individuals without diabetes. In this Perspective, we critically evaluate and argue that this is due to a dysregulated renin-angiotensin system (RAS). Previously, we have shown that loss of angiotensin-I converting enzyme 2 (ACE2) promotes the ACE/angiotensin-II (Ang-II)/angiotensin type 1 receptor (AT1R) axis, a deleterious arm of RAS, unleashing its detrimental effects in diabetes. As suggested by the recent reports regarding the pathogenesis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), upon entry into the host, this virus binds to the extracellular domain of ACE2 in nasal, lung, and gut epithelial cells through its spike glycoprotein subunit S1. We put forth the hypothesis that during this process, reduced ACE2 could result in clinical deterioration in COVID-19 patients with diabetes via aggravating Ang-II–dependent pathways and partly driving not only lung but also bone marrow and gastrointestinal pathology. In addition to systemic RAS, the pathophysiological response of the local RAS within the intestinal epithelium involves mechanisms distinct from that of RAS in the lung; however, both lung and gut are impacted by diabetes-induced bone marrow dysfunction. Careful targeting of the systemic and tissue RAS may optimize clinical outcomes in subjects with diabetes infected with SARS-CoV-2.